2012
DOI: 10.1007/s00231-012-1093-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of sodium sulphate crystallization in porous materials

Abstract: The experimental setup was constructed to measure the thermal effect of the salt crystallization/dissolution process in building materials containing sodium sulphate. Additional heat was released/consumed during the salt crystallization/dissolution. The mathematical model of salt, moisture and energy transport concerning the salt phase change kinetics was derived and based on it the computer code was developed. To solve the set of partial differential, governing equations the finite element and finite differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Therefore, a very accurate value of this threshold should be carefully evaluated experimentally for each specific case. However, given that its influence on the overall response appears not particularly significant (as also experienced by the Authors for values comprised between 1 and 1.7), it is common to adopt a unit value also for the threshold of supersaturation ratio for primary crystallization [42,35,43,44]. This value has been used also in the following.…”
Section: Evolution Equationmentioning
confidence: 99%
“…Therefore, a very accurate value of this threshold should be carefully evaluated experimentally for each specific case. However, given that its influence on the overall response appears not particularly significant (as also experienced by the Authors for values comprised between 1 and 1.7), it is common to adopt a unit value also for the threshold of supersaturation ratio for primary crystallization [42,35,43,44]. This value has been used also in the following.…”
Section: Evolution Equationmentioning
confidence: 99%
“…There is also valuable research presenting theoretical models, numerical simulations and quantitative studies on crystal growth in porous building materials in general [29][30][31][32][33][34][35] and in bricks and mortars in particular [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that during freezing there always remains a thin liquid layer between ice and pore wall [5,6]. The in-pore crystallization is concerned as the major cause of material's microstructure damage, which is why it is a frequent subject of scientific research [7][8][9][10][11]. In vast majority of papers authors assume that temperature changes so slow that considered system remains in thermodynamic equilibrium [12,13].…”
Section: Introductionmentioning
confidence: 99%